Pengaruh Perputaran Kas, Perputaran Piutang, Perputaran Persediaan, dan Leverage Terhadap Profitabilitas Pada Perusahaan farmasi Yang Terdaftar di Bursa Efek Indonesia - Fuji Kurniawan; Rande Samben; Yunita Fitria (Jurnal Ilmu Akuntansi Mulawarman (JIAM), 2020)
Fuji Kurniawan. Influence of Cash Turnover, Accounts Receivable Turnover, Inventory Turnover, and Leverage to the Profitability in Pharmaceutical Companies Listed on the Stock Exchange (IDX). supervised by: Rande Samben, and Yunita FitriaManagement of working capital is very influential on a company's ability to generate profits (profitability). Management of working capital to be more efficient, it can be seen from the rotation of each working capital it self. This research is meant to test the influence of cash turnover, accounts receivable turnover, inventory turnover, and leverage to the profitability. This research uses secondary data taken from the financial statements of manufacturing companies period 2013-2017. Based on the purposive sampling method there are 8 samples according to the criteria. This study used multiple linear regression analysis. The data obtained were analyzed using SPSS statistics 21 software.Based on the result of the test, it showed that: 1) Cash Turnover had unable significant impact on the Profitability, 2) Accounts Turnover had significant impact on the Profitability, 3) Inventory Turnover had significant impact on the Profitability, 4) Leverage had significant impact on the Profitability .